The Effect Of Atypical Antipsychotic Administration On Weight Changes In Patients With Mood Disorders At Dadi Regional Special Hospital, South Sulawesi Province - Lianda Gustisa; Rachmat Faisal Syamsu; Ilma Khaerina Amaliyah; Muh.Alim Jaya; Muh.Wirasto (Jurnal EduHealth, 2025)
Antipsychotic medications are often used to treat mood disorders. Atypical antipsychotics are currently the first-line treatment for patients with mood disorders. However, they can have side effects, significant metabolic side effects, such as central adiposity and weight gain. This study was conducted with the aim of analyzing the Effect of Atypical Antipsychotic Administration on Weight Change in Mood Disorder Patients at the Dadi Regional Special Hospital, South Sulawesi Province. Using descriptive research design with cross sectional method, with a sample of 27 informants. The results of the study. The results showed a significant difference between body weight before and after treatment, the provision of atypical antipsychotic therapy for 1 month showed significant changes in weight measurements of patients with mood disorders on average 0.5 kg - 2 kg. Giving atypical antipsychotic therapy for 2 months showed significant changes in weight measurements of patients with mood disorders on average 2 kg - 5 kg.